Do Corporate Tax Cuts Increase Income Inequality - Suresh Nallareddy; Ethan Rouen; Juan Carlos Suárez Serrato (Center for Economic Studies and ifo Institute (CESifo), 2019)
We study the effects of corporate taxes on income inequality. Using state corporate taxes as a setting, we provide evidence that corporate tax cuts lead to increases in income inequality. This result is robust across regression, matching, and synthetic controls approaches, and to controlling for a host of potential confounders. We use Statistics of Income data from the IRS to explore mechanisms behind this result. We find tax cuts lead to higher income for both top and bottom earners, but the gains to capital income for top earners exceed the gains to total income for bottom earners. This result suggests that, while all earners appear to benefit from a corporate tax cut, the relation between tax cuts and inequality is positive, in part, because high income individuals shift their compensation to reduce taxes.
Keywords: H25; H71; D63; 330; inequality; corporate tax cuts